Penyelesaian Sengketa Kewenangan Antar Lembaga Negara Non Eksekutif yang Kewenangannya diberikan oleh Undang-Undang: Resolution of Authority Disputes Between Non-Executive State Institutions whose Authority is Granted by Law - Huda, Moh. Choirul; Firdaus, Fahmi Ramadhan (Constitution Journal, 2025)
Resolution of disputes over state institutions' authority is part of the Constitutional Court's authority based on Article 24C paragraph (1) of the 1945 Constitution of the Republic of Indonesia. However, this provision raises problems due to the lack of a juridical space to resolve disputes over authority between institutions whose authority is not derived from the 1945 Constitution. Through a study using normative juridical methods, it was found that disputes over authority between institutions arise due to the lack of a clear blueprint for institutional arrangement, as well as political and institutional interests. On the other hand, the problem of resolving disputes over non-constitutional state institutions can be addressed by improving the Constitutional Court's interpretation in the practice of adjudicating state institution disputes, granting authority by the Supreme Court, or through judicial review of laws Abstrak Penyelesaian sengketa kewenangan lembaga negara merupakan bagian dari kewenangan Mahkamah Konstitusi (MK) dengan dasar ketentuan Pasal 24C ayat (1) UUD NRI 1945. Namun, dalam realitasnya ketentuan tersebut menimbulkan problem karena tidak adanya ruang yuridis untuk menyelesaikan sengketa kewenangan antar lembaga yang kewenangannya tidak bersumber dari UUD 1945. Melalui kajian dengan menggunakan metode yuridis normatif, ditemukan bahwa sengketa kewenangan antar lembaga muncul akibat tidak adanya blueprint yang jelas atas  penataan kelembagaan, serta faktor kepentingan politik, serta institusional. Di sisi lain problem penyelesaian sengketa lembaga negara non-konstitusional dapat diatasi dengan memperbaiki tafsir MK dalam praktik peradilan sengketa lembaga negara, pemberian kewenangan oleh Mahkamah Agung, atau melalui sarana pengujian undang-undang (judicial review).